GAMBARAN PENGARUH IMPLEMENTASI KNOWLEDGE MANAGEMENT TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN PENDAPATAN DAERAH KOTA BANDUNG - Syafarina, Shenny; Senen, Syamsul Hadi; Sumiyati, Sumiyati (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this research is to know the decription the influence of knowledge management implementation toward employee performance in Bandung city revenue Management agency.Design/methodology/approach - The Research design is cross sectional. This research is using descriptive approach with explanatory survey method. The analysis unit is 74 employees. Collecting the data is using questionnaire. Analysis technique used is descriptive technique with using frequency distribution.Finding - Based on the result of research, the results obtained that knowledge managemnt in the category is good with a score 81,9% , and employee performence is in high category with a score 86%.Originality/value - This research giving a basic for understanding work dicipline, work culture and issues on organizatonal citizenship behavior. The difference of this research with the previous research are on the object, variable, theory and references.